Determinants of Clean and Healthy Living Behavior (PHBS) among Elderly in Coastal Communities: The Role of Community Nurses in Health Promotion - Masdalifa Pasaribu; Muhammad Kevin Humala Sakti Siregar (Journal of Public Health Sciences, 2026)
This mixed-methods study investigates the determinants of Clean and Healthy Living Behavior (PHBS) among elderly populations in coastal communities in Indonesia, with a particular focus on the role of community nurses in health promotion. Quantitative data were collected from 125 elderly respondents using structured questionnaires, while qualitative insights were gathered through in-depth interviews and focus group discussions with 17 informants, including elderly individuals, caregivers, and community nurses. The results indicate that education level, socioeconomic status, and access to health information are significant predictors of PHBS adherence among the elderly (p < 0.05). Barriers to PHBS implementation include limited mobility, financial constraints, and a preference for traditional or self-medication practices. Community nurses are found to play a crucial yet moderate role in promoting PHBS, with their effectiveness influenced by personal commitment, interpersonal skills, and the availability of health promotion resources. The study highlights the need for enhanced training and support for community nurses, as well as tailored health promotion strategies that address the unique challenges faced by the elderly in coastal areas. Strengthening community-based health interventions and improving access to health information are recommended to increase PHBS compliance and overall well-being among elderly populations in coastal communities.